INVESTIGATION OF SOME PHYSICOCHEMICAL AND ANTIOXIDANT PROPERTIES OF BEE POLLEN FOR ATHLETES - KARAMAN, Mehmet Rüştü (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2019)
Bee products include honey, pollen, propolis, royal jelly and bee bread consists mainly of carbohydrates (CHO), minerals, and vitamins which are properties that are believed able to improve performance and general human health. Especially, bee pollen can be an effective nutrient source for human body to increase immune functions and antioxidant activity, which is essential for a wide variety of metabolic and physiologic processes. Thus, it is believed that bee pollen can be the best supplement for human nutrition and health, but there is limited information on the ergogenic effects of bee pollen on body performance. The main target of this study was to analyse some energy components together with physicochemical and antioxidant properties of bee pollen to determine its potential as a performance-enhancing energy source for humans. For this aim, some physicochemical and biological values together with antioxidant capacity of bee pollen collected from different regions of Central Asia were investigated. The findings have revealed that bee pollens have an abundance of fenolic substances and antioxidants, which are all important in achieving optimal health and performance. However, it has also been concluded that physicochemical and antioxidant properties of pollen samples were varied depending on the varied geographical locations having different floral sources.